Water and playing facilities as a factor increasing the efficiency of educational and training process of young athletes. - Sitnikova N.S; Tyhovskiy T.A (Kharkov National Pedagogical University, 2011)
It is shown the role of water-game activities to enhance the efficiency of teaching and training process for athletes 10-16 years in the preparatory period and their effects on young athletes. It is proposed a set of exercises and games in the water for a sprinter. The basis of systems put different games, relay races, dynamic and static exercises, exercises on the recovery. Proved that the water-play classes young athletes develop harmoniously reinforce the emotional and physiological quality, improve health and increase the intellectual level.